(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
There is still a great demand for public transportation in Malaysia and express buses are no exception. In order to stay competitive, bus companies must position their image and provide a better service for their customers. This study is intended to identify the position of express buses based on customersâ€™ satisfaction towards the service quality by using Multidimensional Scaling (MDS) and Correspondence Analysis (CA). It is also intended to identify the presence or availability of the services/features/appearances provided by the bus company. Data were collected from 142 passengers using convenience sampling at an undisclosed Express Bus Terminal in Klang Valley. The bus companies included in this study were SExpress, KTB, MExpress, MahExpress, DExpress and CExpress. Multidimensional scaling was used to compare the position of the express buses based on the customersâ€™ satisfaction towards the service quality while correspondence analysis was used to investigate the presence or availability of the services/features/appearances provided by the bus company. Results of the analysis show that KTB has the best performance in terms of its responsiveness and assurance in the service quality whereas SExpress has strong association with empathy service quality. MahExpress performed comparatively well on the tangible service quality. MahExpress is associated with â€œon board entertainmentâ€ and â€œcomfortable rideâ€ whereas MExpress is associated with â€œmore leg space in the busâ€. SExpress and KTB are highly competitive because passengers in the cluster perceived similar services/features regarding â€œdriver informs passengers when the bus arrives at respective bus stationsâ€ and â€œbus has comfortable seatsâ€. In conclusion, both methods have created perceptual maps that illustrate the product positions and their attributes which is important to facilitate marketing of the products and services.